Constructing community to achieve citizenship using recognition theory, recovery, and citizenship as a reflective lens: Experiences from the United States and Scotland. Issue 3 (3rd July 2017) - Stewart, Ailsa; Black, Karen; Benedict, Patricia; Benson, Victoria
ABSTRACT: This article explores the usefulness of recognition theory, recovery, and citizenship in explaining constructions of community by adults who have experienced life disruptions participating in similar citizenship programs in the United States and Scotland. A content analysis of secondary data was undertaken and focus groups held with recent graduates of both programs. The findings indicate that constructions of community aligned significantly with aspects of identity and common experience rather than location. Moving toward an identity framed by assets rather than deficits was further identified, which reflects the need for recognition to be extended by communities that are well informed and nondiscriminatory in their attitudes toward those with life disruptions to promote inclusion and connectedness. Interventions at the level of community development and engagement are therefore crucial in promoting inclusion and increasing citizenship for marginalized groups alongside the role of social movements and public policy in tackling stigma and discriminatory attitudes. Uniquely, within this project, a theoretical framework that combined elements of recognition theory, recovery, and citizenship emerged that best explained the experience of those with life disruptions and provided direction for a future focus on community development as well as recovery and citizenship-oriented practice.